Construction and empirical analysis of a quantitative model on the relationship between budget control and financial performance in management accounting—Evidence from Russian enterprises - Ning Tie (PLoS ONE, 2026)
Currently, many enterprises face issues in budget management, such as superficial budgeting, lax execution, and insufficient feedback, leaving the mechanism linking budgetary control and financial performance unclear. Drawing on management accounting and financial management theories, this study constructs a research model encompassing direct, mediating, and moderating effects and conducts a quantitative empirical analysis using Russian enterprises as the research sample. Empirical analyses are conducted using both publicly available data from the Russian Financial Statements Database (RFSD) ( https://github.com/irlcode/RFSD ) and the collected survey data. In terms of variable measurement, budget control is evaluated across three dimensions—budget formulation, execution, and feedback—with mean scores ranging from 3.7 to 3.9, indicating that most enterprises place considerable emphasis on the establishment of budgeting systems. The mean financial performance score ranges from 3.5 to 3.6, suggesting a moderately favorable performance level. Empirical results reveal a significant positive correlation between budget control and financial performance (r > 0.5). In the regression model, the coefficient of budget control is significantly positive, and the explanatory power of the model increases from 0.183 to 0.361 after incorporating budget control, confirming its direct contribution to performance improvement. Further mediation analysis indicates that resource allocation efficiency and internal management processes serve as significant intermediaries between budget control and financial performance, with indirect effects accounting for 29.4% of the total effect. This suggests that budget control primarily enhances performance indirectly by improving internal management mechanisms. The moderation analysis shows that, within the Russian institutional environment, firm size and governance structure strengthen the positive impact of budget control, whereas external environmental uncertainty weakens it. These findings provide empirical evidence for understanding the performance effects of budget control under specific institutional and economic contexts and offer practical guidance for optimizing budget management in Russian enterprises and other transitional economies.